Tracking the history of Waldorf education in Iceland - Adriana Josefina Binimelis Sáez 1966- (2014)
In this electronic version the spelling of the Icelandic abstract was corrected, as well as the format of the references. The two printed versions in the library will show the original mistakes. In Iceland there are two Waldorf primary schools and three pre-schools. In spite of having existed for almost two decades, this pedagogy is scarcely known locally, and there is no written information on the work done by these schools. Wishing to contribute to fill in this gap, in this study I aimed to answer the question: ‘What has been the development of Waldorf education in Iceland?’ To accomplish this task, I gathered information on the events that led to the creation of these educational settings, their founders’ motivations to become involved with this pedagogy, and what have been the main challenges and strengths when implementing this pedagogy. Following the qualitative research tradition, I interviewed six Icelandic Waldorf educators, who have been working for more than ten years in the field. Thus, the study was essentially exploratory and empirical, privileging a phenomenological perspective. The interviews were transcribed and analysed using open coding. The first Steiner/Waldorf educative initiative occurred in 1930 when Sólheimar was founded as an orphanage for normal and disabled children. A group of Icelanders was inspired by this project, and by the anthroposophic community in Jarna (Sweden), which led in 1990 to the formation of Lækjarbotnar (Kópavogur). Their main motivation was to provide Waldorf education to their own children. In 1994, due to different views towards the future, the founding group split, leading to the creation of Sólstafir (Reykjavik). Since then, both initiatives have been providing Waldorf pedagogy from pre-school level to 10th grade. They aim to provide a holistic education, where each child is supported in her process of unfolding her capacities. Thus, the human faculties of thinking, feeling and willing are nurtured simultaneously, by integrating artistic and intellectual ...